2023
DOI: 10.3389/fpubh.2022.1055406
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and financial performance: Pre and post effect of COVID-19 on organization performance; A study based on South Asian economy

Abstract: The COVID-19 epidemic has damaged developing as well as developed economies and reduced the profitability of several companies. Technological advancement plays a vital role in the company's performance in this current situation. All activities carry on virtually. In this study, the financial performance of enterprises in the South Asian banking industry will be compared before and after the COVID-19 epidemic. Furthermore, the full influence of the pandemic will take place in the long run. This study also expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…[18] conducted a study to investigate the share market prices are related to specific events and found the significant relationship between them. According to [19] that the COVID-19 has significant negative and positive impact on the performance of organizations, and they also concluded that some companies maintained their sustainability even though most of the firms suffered from the pandemic. Moreover, [20] investigated the impact on the COVID-19 on the three different stock markets belong to different region such as Pakistan, China and the USA and found the significant negative relationship between the COVID-19 and stock market.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…[18] conducted a study to investigate the share market prices are related to specific events and found the significant relationship between them. According to [19] that the COVID-19 has significant negative and positive impact on the performance of organizations, and they also concluded that some companies maintained their sustainability even though most of the firms suffered from the pandemic. Moreover, [20] investigated the impact on the COVID-19 on the three different stock markets belong to different region such as Pakistan, China and the USA and found the significant negative relationship between the COVID-19 and stock market.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…The COVID-19 pandemic had a substantial impact on the bank's financial performance, notably in terms of profitability, according to Syed Usman Qadri et al (2023). But as technology advances, organisational effectiveness improves, which eventually boosts the financial performance of South Asian banks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This situation makes sectors such as the material sector vulnerable as these firms provide supplies to the construction sector. However, developments such as technological adaptation could curtail the negative Covid-19 impact on profitability (Qadri et al, 2022). Therefore, the real Covid-19 impact on material sector needs to be examined.…”
Section: Literature and Hypothesis Developmentmentioning
confidence: 99%